Pengembangan Media Pembelajaran Berbasis Android Pada Materi Dasar-Dasar Fotografi di SMK Kelas X Program Keahlian RPL - Edy Setyawan, Antonius; Amirul Huda, Fatkhan; Septerio, Alafh Deo (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This research is motivated by the low enthusiasm of learning of X RPL class students of SMK Negeri 1 Belimbing when not using learning media. The purpose of this research is to develop Android-based learning media on photography basics material to increase interest and learning effectiveness. The method used is research and development (R&D) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The results of media expert validation of 96.67% and material experts of 93.75%, indicating the media is classified as very feasible. Student responses to the media were also very positive, with an average of 88% in the small-scale test and 83.67% on a wide scale. The increase in learning interest can be seen from the pre-test and post-test results, both in the experimental and control classes. The t-test showed a significance value of 0.003, which means the media is effective to use. The effectiveness test result of 0.773 is in the medium category. This media is proven to be able to increase students' interest in learning. This research is expected to be a reference in developing other technology-based learning media